2010
DOI: 10.1038/leu.2010.208
|View full text |Cite
|
Sign up to set email alerts
|

TP53 mutation profile in chronic lymphocytic leukemia: evidence for a disease specific profile from a comprehensive analysis of 268 mutations

Abstract: The TP53 mutation profile in chronic lymphocytic leukemia (CLL) and the correlation of TP53 mutations with allele status or associated molecular genetics are currently unknown. We performed a large mutation analysis of TP53 at four centers and characterized the pattern of TP53 mutations in CLL. We report on 268 mutations in 254 patients with CLL. Missense mutations appeared in 74% of cases compared with deletions and insertions (20%), nonsense (4%) and splice site (2%) mutations. The majority (243 of 268) of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
107
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 35 publications
7
107
1
4
Order By: Relevance
“…CLL patients carrying a del(17p) show marked resistance against chemotherapy. Mutations of TP53 are found in 4-37% of patients with CLL, and have been associated with very poor prognosis [19].…”
Section: Introductionmentioning
confidence: 99%
“…CLL patients carrying a del(17p) show marked resistance against chemotherapy. Mutations of TP53 are found in 4-37% of patients with CLL, and have been associated with very poor prognosis [19].…”
Section: Introductionmentioning
confidence: 99%
“…This pattern is similar to what has been reported for 26 608 TP53 mutations in cancer in general in the IARC database, including DLBCL and CLL, although the latter had a lower prevalence of transitions at CpG sites (15%). 13 The exons most frequently targeted by mutations were exons 8 (n ¼ 26) and 5 (n ¼ 21), followed by exons 7 (n ¼ 13), 6 (n ¼ 8) and 4 (n ¼ 1) (Figure 1a). The codons most frequently hit by mutations were at positions 176, 248 and 273 (Figure 1b), which indicates that the classical mutation hot spots are also commonly affected in MCL.…”
mentioning
confidence: 99%
“…We trained an ensemble of decision trees 11,12 (Random Forest) with 3285 likely oncogenic somatic missense mutations from the COSMIC database 13 and 3300 'passenger' mutations synthetically generated by a computer algorithm to mimic the cancer mutation spectrum. To ensure an unbiased score, 13 unique BRAF amino…”
mentioning
confidence: 99%
“…17 Intriguingly, in this study we found that CLL with trisomy 12 was characterized by low levels of P53. As cells that harbor mutations of P53 show strong induction of the aberrant P53 tumor suppressor protein, 22,32,33 our finding of low levels of P53 protein in CLL cases with trisomy 12 fits with an absence of P53 mutations in this subgroup. The levels of other proteins involved in response to DNA damage, such as ATM and RB, were also different in CLL cases with trisomy 12, although only as a trend (Figure 2).…”
Section: Discussionmentioning
confidence: 50%
“…31 Cases with trisomy 12 rarely show P53 mutations or acquire these over time. 32 In addition, CLL with trisomy 12 seems to be more sensitive to chemotherapy than other genetic subgroups of CLL. 17 Intriguingly, in this study we found that CLL with trisomy 12 was characterized by low levels of P53.…”
Section: Discussionmentioning
confidence: 99%